Modeling Macroeconomic Policymakers' Interactions under Zero Lower Bound Environment: The New Keynesian Theoretical Approach - Aleksandra Praščević; Milutin Ješić (Journal of Central Banking Theory and Practice, 2019)
The paper examines how the implicit coordination mechanisms between the policymakers could help in overcoming negative macroeconomic consequences which are provoked by the problem of zero lower bound (ZLB) on the nominal interest rates. For the long period of time, before the global recession started, the ZLB problem was not found to be interesting for researchers. Immediately after the crisis outbreak, more attention was put on that problem within different approaches since conventional monetary policy faced substantial limitation in overcoming business cycles. Many authors have proposed new unconventional measures in both monetary policy and fiscal policy sphere. The theoretical approaches to the ZLB problem include many different aspects. In the paper we chose to use regime switching models adjusted to simulate occasionally binding constraints in order to investigate different scenarios within the New Keynesian framework. We found that coordination between more passive monetary policymaker and more active fiscal policymaker is crucial in the ZLB environment. Central bank has to follow monetary policy rule in which both inflation stabilization and output stabilization have certain positive weight. However, credible policymaking which is supported by the relevant institutions is a necessary precondition for implicit coordination, which substantially decrease the losses occurred as a consequence of ZLB on interest rates.
Keywords: C63; E17; E52; E63; 330; zero lower bound (ZLB); global recession; macroeconomic policymakers' interactions; New Keynesian model.